Cloud-Based Digital Invoice Automation Improves Accuracy and Efficiency for Small and Medium Enterprises: Otomatisasi Invoice Digital Berbasis Cloud Meningkatkan Akurasi dan Efisiensi Usaha Kecil dan Menengah - Wicaksono, Ryan Dwi; Soraya, Dila Umnia (Universitas Muhammadiyah Sidoarjo, 2026)
Manual invoice management in SMEs often leads to delays, recording errors, and difficulty tracking documents. CV Mata Timur Nusantara still uses spreadsheets without a centralized system, making the administration process less efficient. This study developed a cloud-based digital invoice automation system to improve transaction accuracy and efficiency. The development method used the Waterfall model, including analysis, design, implementation, and testing. The system was designed using Laravel, React, and n8n workflow automation integration to automatically create and send PDF invoices through various communication channels. Test results showed that this solution was able to accelerate processes, reduce recording errors, and improve the consistency of document distribution. These findings prove that cloud-based automation is effective in SMEs to support faster and more accurate administration processes. Highlights• Accelerates invoice processing and distribution for SMEs• Reduces manual recording errors through automated workflow• Improves consistency and reliability of document delivery KeywordsDigital Inovice; Workflow Automation; Cloud Computing; Information System; Application Integration